Potencial evocado auditivo de tronco encefálico em equinos - Da Gama, Juliana Almeida Nogueira [UNESP]; Palumbo, Mariana Isa Poci; Olivo, Giovane [UNESP]; Outeda, Nadia Crosignani [UNESP]; Resende, Luiz Antônio de Lima; Borges, Alexandre Secorun [UNESP] (FapUNIFESP (SciELO), 2016)
The brainstem auditory evoked potential (BAEP) evaluates the integrity of the auditory pathways to the brainstem. The aim of this study was to evoke BAEPs in 21 clinically normal horses. The animals were sedated with detomidine hydrochloride (0.013mg.kg-1 BW). Earphones were inserted and rarefaction clicks at 90 dB and noise masking at 40 dB were used. After performing the test, the latencies of waves (I, II, III, IV, and V) and interpeaks(I- III, III-V, and I-V) were identified. The mean latencies of the waves were as follows: wave I, 2.4 ms; wave II, 2.24 ms; wave III, 3.61ms; wave IV, 4.61ms; and wave V, 5.49ms. The mean latencies of the interpeaks were as follows: I-III, 1.37ms; III-V, 1.88ms; and I-V, 3.26ms. This is the first study using BAEPs in horses in Brazil, and the observed latencies will be used as normative data for the interpretation of tests performed on horses with changes related to auditory system or neurologic abnormalities.
Brainstem auditory evoked potentials in horses
Keywords: Deafness; Horses; Interpeaks; Latency